Evaluation of the Effectiveness of Kredit Usaha Rakyat (KUR) Policy in Encouraging Economic Growth and Social Welfare in Central Java Province - Werdha Candratrilaksita; Hartuti Purnaweni; Kismartini Kismartini (Universitas Terbuka, 2020)
In 2018, Central Java could only absorb 26.22% of KUR distribution in the production sector. The Non-Performing Loan (NPL), released by the Financial Services Authority, presented a lower production sector NPL than the trade sector. The agricultural sector was 1.85%, the manufacturing sector was 3.19%, and the trade sector was 4.45%. In 2017, NPL of KUR Micro and Retail KUR of the agricultural sector amounted to 0.76%, while the trade sector amounted to 1.44%. The problem raised research questions: 1) Did the banks which distributed KUR and the Guarantor Institution experience a conflict of interest - between the public interest (the duty of the state to extend credit to MSMEs) and the interests of corporate entities (the task of seeking profits and avoiding risk), 2) Why was the lending of KUR in the production sector lower than the lending of KUR in the trade sector, and 3) How effective was KUR on economic growth and social welfare. To answer the research questions, researchers used a descriptive qualitative approach. Purposive sampling technique was used in this study. The finding showed dumping pricing policy tended to be misused by the banks which distributed KUR, and there was a conflict of interest and risk transfer in giving KUR. However, Small and Medium-sized Enterprises (UMKM) entrepreneurs who received KUR admitted that their profit was increased which also meant the improvement of social welfare.